Association Between Antidiabetic Pattern with Medication Adherence in Type 2 Diabetes Patients at Buleleng Hospital: Hubungan Antara Pola Penggunaan Antidiabetik dengan Kepatuhan Pengobatan Pada Pasien Diabetes Melitus Tipe 2 Di Salah Satu Rumah Sakit Swasta Buleleng Bali - Ratnasari, Pande Made Desy; Ardeliani, I Gusti Ayu Indira; Yuliawati, Agustina Nila; Kurnianta, Putu Dian Marani (Universitas Tadulako, 2023)
Background: Type 2 diabetes mellitus (DM) is a chronic disease which requires long-term therapy. Medication adherence plays an important role for therapeutic success in patients with T2DM. Antidiabetic usage pattern might involve with some problems related to medication adherence. Objectives: The aim of this study was to analyze the association between antidiabetic usage pattern with medication adherence. Material and Methods: This observational study was conducted cross-sectionally involving 90 participants of T2DM outpatient at Private Hospital in Buleleng Bali during July-September 2020. Patients were included if aged â‰¥18 years, received the same antidiabetic for three months before the study, signed informed consent, and provided with complete medical record data. Patients were excluded if appeared to be unwell, pregnant or breastfeeding. Demographic data and antidiabetic usage patterns were collected retrospectively based on the patient's medical records. Probabilistic Medication Adherence Scale (ProMAS) questionnaire was used to assess medication adherence. Data were analyzed with Kruskal-Wallis test. Results: The results showed that 55.6% patients were male, aged 46-65 years (61.1%), education predominantly by elementary school (37.8%), had suffered from DM for 5-10 years (46.7%), with comorbidities (50%), and without complications (77.8%). The antidiabetic usage pattern was dominated by a combination of two antidiabetics (53.3%). Most patients (42.2%) showed moderate-high medication adherence. There was no statistically significant association between antidiabetic usage pattern and medication adherence (p=0.275). Conclusions: A higher rate of medication adherence was found in patients taking combination of two antidiabetics compared to combination of three or four antidiabetics.